Higher-order income risk over the business cycle - Christopher Busch; Alexander Ludwig (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2021)
We extend the canonical income process with persistent and tran- sitory risk to cyclical shock distributions with left-skewness and excess kurtosis. We estimate our income process by GMM for US household data. We find countercyclical variance and procyclical skewness of per- sistent shocks. All shock distributions are highly leptokurtic. The tax and transfer system reduces dispersion and left-skewness. We then show that in a standard incomplete-markets life-cycle model, first, higher- order risk has sizable welfare implications, which depend on risk atti- tudes; second, it matters quantitatively for the welfare costs of cyclical idiosyncratic risk; third, it has non-trivial implications for self-insurance against shocks.
Keywords: 330; Idiosyncratic Income Risk; Cyclical Income Risk; Life-Cycle Model